Violence and conservation: Beyond unintended consequences and unfortunate coincidences (2016)
While the relationship between violence and conservation has gained increasing attention in both academic and activist circles, official and public discourses often portray their entanglements as (unlucky) overlapping phenomena. In this article, we show how, under specific practices of state territorialization, conservation becomes both the means and reasons for violence. Based on ethnographic research in Colombia's emblematic Tayrona National Natural Park, we detail how both the war on drugs and tourism promotion shape these state practices, and how they have translated into everyday, yet powerful, means of dispossession in the name of conservation. By analyzing the effects of the production of peasants as environmental predators, illegal occupants and collateral damage, we show how official conservation strategies have justified local communities' political and material erasure, and how they have resulted in the destruction of their lived ecologies and the erosion of their livelihood strategies. © 2015 Elsevier Ltd.